The Role Of BK Teachers In Increasing Students' Self-Confidence Through Group Counseling At MAN 1 Medan - Nasution, Risdani Putri; Manurung, Purbatua; Daulay, Afrahul Fadhila (Jurnal Pendidikan Indonesia, 2023)
This type of research uses descriptive qualitative research. This research uses a descriptive qualitative approach, because the researcher wants to describe the actual role of guidance and counseling teachers in increasing students' self-confidence through group guidance. This approach was also chosen because it allows researchers to collect data and adapt it to the context.The data sources used to obtain research data are divided into two,namely primary data sources and secondary data sources.Then the data collection techniques used are observation, interviews and documentation.In this research, the problem formulation is the level of student self;confidence, what factors cause distrust, how group guidance is implemented, funds and the role of guidance and counseling teachers in increasing student self;confidence through group guidance.Group guidance services are very important to be implemented in schools because they suit the various needs of students.Among them is that through group guidance students can increase their self-confidence.Because the aim of group tutoring services is for students to have the courage to express their opinions in public which then leads students to achieve learning success according to what they want.